2013
DOI: 10.1387/revpsicodidact.7127
|View full text |Cite
|
Sign up to set email alerts
|

Student, Teacher, and School Context Variables Predicting Academic Achievement in Biology: Analysis from a Multilevel Perspective // Variables del estudiante, del profesor y del contexto en la predicción del rendimiento académico en Biología: Análisis ...

Abstract: ResumenEn el presente estudio se analiza la contribución de variables del alumno y variables del contexto en la predicción del rendimiento académico en Bachillerato. Se han obtenido información de 988 estudiantes, de último curso de Bachillerato y de sus 57 profesores de Biología. Los datos fueron analizados desde una perspectiva multinivel. Los resultados indican que, de la variabilidad observada en el rendimiento en Biología, el 85.6% se debe a las variables de nivel de estudiante mientras que el 14.4% resta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
2
12
1
9
Order By: Relevance
“…Similarly, there are studies which indicate that homework behavior can vary depending on the topic studied (Trautwein & Lüdtke, 2007, 2009. In this century, multilevel studies have refined this relationship and shown that time spent has little effect on results (De Jong, Westerhof, & Creemers, 2000;Farrow, Tymms, & Henderson, 1999;Murillo & Martínez-Garrido, 2013;Núñez, Vallejo, Rosário, Tuero, & Valle, 2014) and, with statistical significance, the effect is negative (Chang, Wall, Tare, Golonka & Vatz, 2014;Trautwein, 2007;Trautwein, Köller, Schmitz, & Baumert, 2002;Trautwein, Schnyder, Niggli, Neumann, & Lüdtke, 2009). These studies show that students who have more difficulty learning or concentrating need more time to do their homework.…”
Section: Student Homework Behaviourmentioning
confidence: 99%
“…Similarly, there are studies which indicate that homework behavior can vary depending on the topic studied (Trautwein & Lüdtke, 2007, 2009. In this century, multilevel studies have refined this relationship and shown that time spent has little effect on results (De Jong, Westerhof, & Creemers, 2000;Farrow, Tymms, & Henderson, 1999;Murillo & Martínez-Garrido, 2013;Núñez, Vallejo, Rosário, Tuero, & Valle, 2014) and, with statistical significance, the effect is negative (Chang, Wall, Tare, Golonka & Vatz, 2014;Trautwein, 2007;Trautwein, Köller, Schmitz, & Baumert, 2002;Trautwein, Schnyder, Niggli, Neumann, & Lüdtke, 2009). These studies show that students who have more difficulty learning or concentrating need more time to do their homework.…”
Section: Student Homework Behaviourmentioning
confidence: 99%
“…Cabe aquí indicar que el uso de este tipo de técnicas se ha generalizado de manera notable para el análisis de la información en muchas de las investigaciones llevadas a cabo en el campo de la educación. Así, diversos métodos de clasificación o de predicción han sido propuestos por diferentes autores, como el análisis cluster (Valle et al, 1997), éste combinado con el Análisis de la Varianza, ANOVA, (Palacios Picos, López Pastor y Barba, 2013), el análisis de componentes principales (Elosua, López-Jáuregui, Bully y Mujika., 2012), el modelado estadístico (Núñez, Vallejo, Rosário, Tuero y Valle, 2014) y regresión múltiple junto con un ANOVA (Urquidi Martín y Calabor Prieto, 2014).…”
Section: Objetivounclassified
“…En cualquier caso y en términos generales, se constatan diferencias significativas en los resultados académicos atendiendo a si la metodología utilizada es tradicional o innovadora, a favor de esta última (Saiz y Román, 2011). Sin embargo cabe reflexionar acerca de la idoneidad de relegar a un segundo puesto los enfoques tradicionales de enseñanza (Cid Sabucedo, Pérez Abellás y Zabalza Beraza, 2013).…”
Section: Referentes Teóricosunclassified
See 1 more Smart Citation
“…This meaning depends on personal factors such as values, interests, goals, expectancies and self-regulation ability (Alonso-Tapia, 2005;Alonso-Tapia, Huertas, & Ruiz, 2010;Alonso-Tapia, Nieto, & Ruiz, 2013;Alonso-Tapia, Panadero, & Ruiz, 2014;Assor, Kaplan, & Roth, 2002;Núñez et al, 2014;Patrick, Kaplan, & Ryan, 2011;Covington, 2000;Deci & Ryan, 2002;Eccles & Wigfield, 2002;Elliot, 2005;Zimmerman & Schunk, 2008). These values and interests change depending on social conditions such as parents' socio-cultural level or being or not an immigrant (Alonso-Tapia & Simón, 2012;Franzé, 2002;Salili & Hoosain, 2007), as well as on factors defining instructional environment and configuring classroom motivational climate (AlonsoTapia & Pardo, 2006;De Corte, Verschaffel, Entwistle, & van Merriënboer, 2003;Urdan & Turner, 2005).…”
Section: Introductionmentioning
confidence: 99%